Cantilever signature of tip detachment during contact resonance AFM - Kalafut, Devin; Wagner, Ryan; Cadena, Maria Jose; Bajaj, Anil; Raman, Arvind (Beilstein Journal of Nanotechnology, 2021)
Contact resonance atomic force microscopy, piezoresponse force microscopy, and electrochemical strain microscopy are atomic force microscopy modes in which the cantilever is held in contact with the sample at a constant average force while monitoring the cantilever motion under the influence of a small, superimposed vibrational signal. Though these modes depend on permanent contact, there is a lack of detailed analysis on how the cantilever motion evolves when this essential condition is violated. This is not an uncommon occurrence since higher operating amplitudes tend to yield better signal-to-noise ratio, so users may inadvertently reduce their experimental accuracy by inducing tip–sample detachment in an effort to improve their measurements. We shed light on this issue by deliberately pushing both our experimental equipment and numerical simulations to the point of tip–sample detachment to explore cantilever dynamics during a useful and observable threshold feature in the measured response. Numerical simulations of the analytical model allow for extended insight into cantilever dynamics such as full-length deflection and slope behavior, which can be challenging or unobtainable in a standard equipment configuration. With such tools, we are able to determine the cantilever motion during detachment and connect the qualitative and quantitative behavior to experimental features.
Keywords: atomic force microscopy (AFM); contact resonance; nonlinear normal mode (NNM); tip–sample detachment; photothermal excitation

Applied Scanning Probe Methods XI: Scanning Probe Microscopy Techniques - Hurley, D. C. (Contact resonance force microscopy techniques for nanomechanical measurements, 2009)

Applied Scanning Probe Methods II: Scanning Probe Microscopy Techniques - Rabe, U. (Atomic force acoustic microscopy, 2006)

(untitled) - Soergel, E. (J. Phys. D: Appl. Phys., 2011)

(untitled) - Balke, N.; Jesse, S.; Morozovska, A. N.; Eliseev, E.; Chung, D. W.; Kim, Y.; Adamczyk, L.; García, R. E.; Dudney, N.; Kalinin, S. V. (Nat. Nanotechnol., 2010)

(untitled) - Binnig, G.; Quate, C. F.; Gerber, C. (Phys. Rev. Lett., 1986)

(untitled) - Killgore, J. P.; DelRio, F. W. (Macromolecules, 2018)

(untitled) - Efremov, Y. M.; Okajima, T.; Raman, A. (Soft Matter, 2020)

(untitled) - Cadena, M. J.; Chen, Y.; Reifenberger, R. G.; Raman, A. (Appl. Phys. Lett., 2017)

(untitled) - Killgore, J. P.; Kelly, J. Y.; Stafford, C. M.; Fasolka, M. J.; Hurley, D. C. (Nanotechnology, 2011)

(untitled) - Ma, C.; Chen, Y.; Arnold, W.; Chu, J. (J. Appl. Phys., 2017)

(untitled) - Wang, W.; Ma, C.; Chen, Y.; Zheng, L.; Liu, H.; Chu, J. (Beilstein J. Nanotechnol., 2019)

(untitled) - Ma, C.; Wang, W.; Chen, Y.; Arnold, W.; Chu, J. (J. Appl. Phys., 2019)

(untitled) - Kalinin, S. V.; Bonnell, D. A. (Phys. Rev. B, 2002)

(untitled) - Kalinin, S. V.; Shao, R.; Bonnell, D. A. (J. Am. Ceram. Soc., 2005)

(untitled) - Bonnell, D. A.; Kalinin, S. V.; Kholkin, A. L.; Gruverman, A. (MRS Bull., 2009)

(untitled) - Jin, L.; Li, F.; Zhang, S. (J. Am. Ceram. Soc., 2014)

(untitled) - O’Hayre, R.; Lee, M.; Prinz, F. B. (J. Appl. Phys., 2004)

(untitled) - Jesse, S.; Kumar, A.; Arruda, T. M.; Kim, Y.; Kalinin, S. V.; Ciucci, F. (MRS Bull., 2012)

(untitled) - Morozovska, A. N.; Eliseev, E. A.; Balke, N.; Kalinin, S. V. (J. Appl. Phys., 2010)

(untitled) - Turner, J. A. (J. Sound Vib., 2004)

(untitled) - Vairac, P.; Boucenna, R.; Le Rouzic, J.; Cretin, B. (J. Phys. D: Appl. Phys., 2008)

(untitled) - Arafat, H. N.; Nayfeh, A. H.; Abdel-Rahman, E. M. (Nonlinear Dyn., 2008)

(untitled) - Kirrou, I.; Belhaq, M. (Nonlinear Dyn., 2015)

(untitled) - Kolosov, O.; Yamanaka, K. (Jpn. J. Appl. Phys., Part 2, 1993)

(untitled) - Yamanaka, K.; Ogiso, H.; Kolosov, O. (Jpn. J. Appl. Phys., Part 1, 1994)

(untitled) - Yamanaka, K.; Noguchi, A.; Tsuji, T.; Koike, T.; Goto, T. (Surf. Interface Anal., 1999)

(untitled) - Muraoka, M.; Arnold, W. (JSME Int. J., Ser. A, 2001)

Proceedings of the International Symposium on Nonlinear Acoustics - Rabe, U.; Kopycinska-Müller, M.; Reinstädtler, M.; Hirsekorn, S.; Arnold, W. (Nonlinear effects in ultrasonic transmission in atomic force microscope contacts, 2002)

(untitled) - Haller, G.; Ponsioen, S. (Nonlinear Dyn., 2016)

(untitled) - Rosenberg, R. M. (J. Appl. Mech., 1960)

(untitled) - Shaw, S. W.; Pierre, C. (J. Sound Vib., 1991)

(untitled) - Butt, H.-J.; Cappella, B.; Kappl, M. (Surf. Sci. Rep., 2005)

(untitled) - Butt, H.-J.; Jaschke, M. (Nanotechnology, 1995)

(untitled) - Derjaguin, B. V.; Muller, V. M.; Toporov, Y. P. (J. Colloid Interface Sci., 1975)

(untitled) - Shaik, N. H.; Reifenberger, R. G.; Raman, A. (Nanotechnology, 2020)

(untitled) - Labuda, A.; Kocuń, M.; Meinhold, W.; Walters, D.; Proksch, R. (Beilstein J. Nanotechnol., 2016)

(untitled) - Sneddon, I. N. (Int. J. Eng. Sci., 1965)

Mechanical Vibrations - Rao, S. S. (Prentice Hall, 2011)

(untitled) - Rabe, U.; Janser, K.; Arnold, W. (Rev. Sci. Instrum., 1996)

(untitled) - Melcher, J.; Hu, S.; Raman, A. (Appl. Phys. Lett., 2007)

(untitled) - Wagner, R.; Killgore, J. P. (Appl. Phys. Lett., 2015)

(untitled) - Labuda, A.; Kobayashi, K.; Kiracofe, D.; Suzuki, K.; Grütter, P. H.; Yamada, H. (AIP Adv., 2011)